2016
DOI: 10.1038/mt.2016.147
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine Selectively Depletes Alloreactive T Cells to Prevent GVHD While Conserving Immunity to Viruses and Leukemia

Abstract: Selective depletion (SD) of alloreactive T cells from allogeneic hematopoeitic stem cell transplants to prevent graft-versus-host disease (GVHD) without compromising immune reconstitution and antitumor responses remains a challenge. Here, we demonstrate a novel SD strategy whereby alloreacting T cells are efficiently deleted ex vivo with adenosine. SD was achieved in human leukocyte antigen (HLA) mismatched cocultures by multiple exposures to 2 mmol/l adenosine over 7 days. Adenosine depleted greater than to 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…In theory, in HID‐SCT, stronger alloimmune response would be achieved by leukemic cells which express HLA mismatched from donors and result in a decrease in relapse rate. However, since little is known about the mechanisms underlying the stronger GVL effect of HID‐SCT compared to that of ISD‐SCT [27‐29], there may be some other possible reasons for the higher relapse rate in the ISD‐SCT group compared to the HID‐SCT group in the current study. First, in the present study, both groups of patients received CSA, MTX, and MMF as GVHD prophylaxis.…”
Section: Discussionmentioning
confidence: 87%
“…In theory, in HID‐SCT, stronger alloimmune response would be achieved by leukemic cells which express HLA mismatched from donors and result in a decrease in relapse rate. However, since little is known about the mechanisms underlying the stronger GVL effect of HID‐SCT compared to that of ISD‐SCT [27‐29], there may be some other possible reasons for the higher relapse rate in the ISD‐SCT group compared to the HID‐SCT group in the current study. First, in the present study, both groups of patients received CSA, MTX, and MMF as GVHD prophylaxis.…”
Section: Discussionmentioning
confidence: 87%
“…We then addressed whether the treatment with Salp15 would impact the activity rather than the size of the Treg population. The ectoenzyme CD73 is expressed by Tregs and mediates the production of adenosine, an immunosuppressive molecule on T cells 29 31 . We observed that expression levels of Nt5e (which encodes CD73) were increased upon the treatment of CD4 T cells with Salp15 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In theory, choosing a donor with greater HLA disparity from the recipient could mitigate the relapse risk induced by a greater allo-immune GVL effect [5,16,28]. However, apart from donor type, many factors can influence GVL [2,22,23,25], including disease type and remission status before HSCT, patient age, conditioning regimen, GVHD prophylaxis, number of T cells infused, presence of GVHD, use of immunotherapy and targeted drugs, and other factors.…”
Section: Discussionmentioning
confidence: 99%